Pemberdayaan Masyarakat Pesisir melalui Implementasi Sistem Peringatan Dini Kenaikan Muka Air Laut Berbasis Sensor Ultrasonik dan WhatsApp - Nur Imansyah; Arfittariah Arfittariah; Zaini Zaini; Abadi Nugroho; Turahyo Turahyo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Tanjung Laut Indah Village, Bontang City, is a coastal area that is vulnerable to sea level rise, high tides, and tidal flooding, making an effective early warning mechanism essential for disaster risk reduction. This Community Service Program (PKM) aims to empower the coastal community through the implementation of an early warning system for sea level rise based on an ultrasonic sensor and WhatsApp notifications. The system employs a waterproof ultrasonic sensor integrated with an ESP32 microcontroller to monitor sea level changes in real time. Measurement data are compared with predefined threshold values to classify conditions into Safe, Advisory, Warning, and Emergency levels. When the measured water level exceeds the specified threshold, the system automatically sends warning messages to community members and relevant stakeholders via WhatsApp. The implementation method includes community needs assessment, system design and installation, user training on system operation and maintenance, and evaluation through functional testing and questionnaires. The expected outcomes are improved community awareness, preparedness, and capacity in responding to coastal hazards, the availability of an easy-to-use early warning system, and the establishment of a rapid, accurate, and sustainable information dissemination mechanism to support community-based disaster mitigation.